EARLY GOAL DIRECTED THERAPY AT SEPTIC SYOK - Widyanti, Ayu; Hartawan, Budi; Suparyatha, IB (Medicina, 2012)
Sepsis is the most commom cause of death in children with critically ill. Using WHO criteria (severe sepsis defined as sepsis with acidosis, hypotension or both), it was determined that in 1995 there were more than 42.000 cases of severe sepsis in children in the United States with mortality rate was 10.3%. To answer that finding, evicende based protocol was made, it called early goal directed therapy (EGDT). EGDT is a comprehensive strategy to evaluate patient with septic shock include, challenge of fluid, antibiotic, vasopressor, measurement of central vein oxygen saturation, PRC transfusion, administering inotropic dan mechanic ventilation. All of these must be done in the first 6 hours since sepsis or septic shock was found, because if there is a delay of resuscitation, anything we do to increase oxygenation level of the cell will be useless.